In vitro ACE2 enzyme inhibitory activity evaluation of different salvia essential oils - Karadağ, Ayşe Esra; Biltekin, Sevde Nur; Demirci, Betül; Demirci, Fatih (Istanbul Medipol University, 2022)
In this present study, commertially available Salvia triloba L., S.officinalis L., and S. sclarea L. essential oils were evaluated for their in vitro angiotensin converting enzyme 2 (ACE2) inhibitory activity. The Salvia essential oils compositions were confirmed both by GC-FID and GC/MS. Main components of the S. triloba essential oil was characterized as 1,8-cineole (22.8%), camphor (17.2%), ?-thujone (15.2 %), ?-caryophyllene (11.4 %), and ?-humulene (3%). Major constiutents were identified as ?-thujone (28.5 %), camphor (20.6 %), 1,8-cineole (10.9%), ?-humulene (5%), and camphene (4.9 %) in S. officinalis essential oil. Whereas, linalylacetate (56.8 %), linalool (21.1%), ?-terpineol (6.1%), geraniol (5%), and ?-caryophyllene (3.4%) were the major components of S. sclarea essential oil. The essential oils were evaluated using a fluorometric multiplate based enzyme inhibition kit, where the ACE2 inhi-bitions of S. triloba, S. officinalis, and S. sclarea essential oils were 50.1%, 60.5%, and 72.1% at a concentration of 20 µg/mL, respectively. As a result, further tests of Salvia essential oils supported by in vivo studies may have antiviral potential ap-plications against coronaviruses due to ACE2 enzyme inhibitions.
Keywords: ACE2; Coronavirus; Essential Oil; Salvia